Heckroccurve: ROC Curves for Selected Samples. (March 2018) - Cook, Jonathan A.; Rajbhandari, Ashish
Receiver operating characteristic (ROC) curves can be misleading when they are constructed with selected samples. In this article, we describeheckroccurve, which implements a recently developed procedure for plotting ROC curves with selected samples. The command estimates the area under the ROC curve and a graphical display of the curve. A variety of plot options are available, including the ability to add confidence bands to the plot.